Predictors of Extubation Success in Patients with Middle Cerebral Artery Acute Ischemic Stroke - Linda C. Wendell; Jonathan Raser; Scott Kasner; Soojin Park (Stroke Research and Treatment)
Introduction. Stroke patients often meet respiratory guidelines for extubation, but uncertainty exists if patients will protect their airway due to impaired mental status. Patients with middle cerebral artery (MCA) acute ischemic stroke (AIS) might have specific predictors of successful extubation. Methods. Retrospective cohort of MCA AIS patients requiring intubation. Results. Thirty-seven MCA AIS patients were extubated successfully and ten failed extubation. Those who successfully extubated had higher extubation composite and eye response Glasgow Coma Scale (GCS) scores compared to those who failed (median 10T (IQR 9T–11T) versus 9.5T (8T–10T), 𝑃=0.047, and 4 (3-4) versus 2.5 (1–3), 𝑃<0.01). When adjusted for age, admission National Institutes of Health Stroke Scale score and laterality, patients with a GCS score ≥8T trended toward extubating successfully (OR 23.30 (CI 0.94–580.27), 𝑃=0.055). Conclusions. The GCS score might be important in predicting successful extubation in MCA AIS patients. Further prospective study is warranted to better assess factors predictive of extubation outcome in stroke and other brain-injured patients.